Polysomnographic Aspects of Sleep Architecture on Self-limited Epilepsy with Centrotemporal Spikes: A Systematic Review and Meta-analysis - Halal, Camila dos Santos; Horta, Bernardo Lessa; Nunes, Magda Lahorgue (Sleep Science, 2017)
Self-limited epilepsy with centrotemporal spikes is the most common paediatric epileptic syndrome, with growing evidence linking it to various degrees and presentations of neuropsychological dysfunction. The objective of this study is to evaluate the possible sleep macro and microstructural alterations in children with this diagnosis. A systematic review of published manuscripts was carried out in Medline, LILACS and Scielo databases, using the MeSH terms epilepsy, sleep and polysomnography. From 753 retrieved references, 5 were selected, and data from macro and, when available, microstructure of sleep were extracted. Meta-analysis was performed with data from 4 studies using standardized mean difference. Findings were heterogeneous between studies, being the most frequent macrostructural findings a smaller proportion and greater latency of REM sleep in two studies and, in meta-analysis, a longer sleep latency was the most significant finding among epileptic patients. Only one study evaluated sleep microstructure, suggesting possible alterations in cyclic alternating pattern in diagnosed children. Studies evaluating macro and microstructure of sleep in children with self-limited epilepsy with centrotemporal spikes are necessary to a better understanding of mechanisms of the neuropsychologic disturbances that are frequently seen in children with this diagnosis.
Keywords: Sleep; Epilepsy; Polysomnography